Threshold effect of Financial Integration on Linkages Between Monetary Independence and Foreign Exchange Reserves - Chee-Hong Law; Chee-Lip Tee; Say Keat Ooi (Asian Academy of Management Journal of Accounting and Finance, 2019)
This paper investigates the relationship between monetary independence and its potential determinants — foreign exchange reserves, exchange rate stability, financial integration and inflation. This paper contributes to the literature by testing the threshold effect of the degree of financial integration on the relation between monetary independence and foreign exchange reserves. In particular, a linear model and a threshold model are compared using average cross-sectional data from 55 countries. The linear model shows that foreign exchange reserves increase monetary independence. Nonetheless, the threshold estimation indicates that foreign exchange reserves can maintain monetary independence when the degree of financial integration of a country is above a certain threshold value. Such a finding suggests that the relationship between monetary independence and foreign exchange reserves is subject to the degree of financial integration. Moreover, the evidence supports a weakening effect from financial integration to the phenomenon of ‘fear of floating’.